(untitled) (Advancements in Homeopathic Research, 2023)
Dyspnoea is shortness of breath or a feeling that you cannot breathe enough air into lungs which can cause tightness in chest. Dyspnoea can be due to exercise which is short term or due to some underlying causes such as respiratory, cardiac, neuromuscular, psychogenic, systemic illness, or their combination.1This article deals with case reported to us with dyspnoea since 3 year. After detailed case taking and repertorisation of case by Boger Boennighausen Characteristics and repertory2, Ipecacuhana was prescribed on the basis of repertorization and in 2 months patient was relieved from her complaints. The assessment was done on Modified Borg Dyspnoea Scale3 and pre treatment it was 5 and post treatment after 2 months 0.5 which shows marked improvement in Dyspnoea.